PENGARUH KUALITAS PELAYANAN, HARGA, DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN PENGGUNA JASA TRANSPORTASI OJEK ONLINE DI LAMONGAN - Nawari Nawari; Sigit Marianto (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2020)
This study aims to determine the effect of service quality, price, brand image on satisfaction of ojek online transportation customers in Lamongan. This study is a survey with quantitative research. The population in this study is Cak Ed Lamongan online motorcycle taxi customers. Sampling used a purposive sampling technique and obtained a sample of 100 respondents using the formula Rao Purba. Data collection techniques in this study used interviews and questionnaires. Analysis of the data used were the validity test, the reliability test, the multiple linear regression analysis, the classic assumption test, the coefficient of determination R2 test, and hypothesis was tested through t test that was used to determine the effect of service quality, price and brand image partially on satisfaction of ojek online transportation customers in Lamongan. From the analysis, results obtained of t test results variable service quality was tcount = 3.934 > ttable = 1.660 which states that the quality of service affects customer satisfaction. Price variable was tarithmetic = 3,622 > ttable = 1,660 which indicates that price influences customer satisfaction, and brand image variable tcount = 2,216 > ttable = 1,660 which states that brand image influences customer satisfaction. While R square of 0.783 shows that 78.3% of the variable Customer satisfaction is influenced by service quality, price, and brand image. While the remaining 21.7% is influenced by other variables that were not examined.